1989
DOI: 10.1111/j.1532-5415.1989.tb06810.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Replacement in Patients Aged 80 Years and Older

Abstract: Total hip replacement was performed in 27 patients aged 80 years and older. In the early postoperative period, medical complications occurred in 13 patients and arthroplasty-related complications in 5 patients. At the time of the follow-up, after an average of 31 months, there was one case of acetabular cup loosening, which was revised. Twenty of 22 patients were free from pain at rest, and the social function of the patients had remained almost unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Similar relationships exist after hip replacement for osteoarthritis. Walking distance increases, 292,293 and gait velocity and step length may improve by up to 100% at 6 months postoperation (with maintenance of improvements by 4 years postoperation) 294,295 . Up to 58% of these patients use no assistive device at 6 months postoperation (88% by 4 years).…”
Section: Gait Disorder Treatment and Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar relationships exist after hip replacement for osteoarthritis. Walking distance increases, 292,293 and gait velocity and step length may improve by up to 100% at 6 months postoperation (with maintenance of improvements by 4 years postoperation) 294,295 . Up to 58% of these patients use no assistive device at 6 months postoperation (88% by 4 years).…”
Section: Gait Disorder Treatment and Rehabilitationmentioning
confidence: 99%
“…Up to 58% of these patients use no assistive device at 6 months postoperation (88% by 4 years). Despite these improvements, patients may still have pain, “limp,” and/or limited walking ability, 292,293 and gait velocity and hip motion are still below standard norms at 6 months postoperation 296 . Two years postoperatively, even in patients with near normal gait velocity, reductions are seen in single limb stance duration and hip motion, abnormal hip muscle EMG patterns are still present, and less force is applied through the operated limb, suggesting persistent leg weakness.…”
Section: Gait Disorder Treatment and Rehabilitationmentioning
confidence: 99%
“…6,7 Small retrospective studies of THR and TKR in patients over the age of 80 report significant pain relief and improved functional outcomes, at a cost of increased rates of post-operative complications and mortality. [8][9][10][11][12][13] Comparative studies have also shown that patients aged 80 years or more experience relief of pain and improvement in function equal to their younger counterparts at follow-up of one year, and the rates of complications were not increased in older age groups. [14][15][16] This study aims to answer whether patients  80 years of age benefit from THR and TKR to the same extent as their younger counterparts, and if this benefit is at the risk of an increased rate of post-operative complications, including mortality.…”
mentioning
confidence: 99%
“…Preoperative medical preparation and intraoperative monitoring allow orthopedic surgery to be carried out safely in patients at any age. Peterson et al 102 reported their experience with total hip replacement in 22 patients aged 80 years and over. Medical complications were present in 13 patients; arthroplasty‐related complications were present in five patients.…”
Section: Surgical Optionsmentioning
confidence: 99%